A primer on viral‐associated olfactory loss in the era of COVID‐19. Issue 7 (1st June 2020) - Soler, Zachary M.; Patel, Zara M.; Turner, Justin H.; Holbrook, Eric H.
Abstract: Early reports have suggested that smell loss may be an early symptom associated with the pandemic known as coronavirus disease 2019 (COVID‐19). The possibility that severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) might cause olfactory dysfunction is certainly plausible. Patients presenting to specialized smell clinics are commonly diagnosed with upper respiratory infection (URI)‐associated olfactory loss and most are presumed to be viral related. In acute phases of infection, it is common to experience some smell loss as a result of nasal inflammation, mucosal edema, and obstruction of airflow into the olfactory cleft. In most cases, these episodes of smell loss are self‐limiting and coincide with resolution of URI symptoms. However, in some cases the smell loss persists for months to years and this is presumed to occur through a more direct olfactory insult by the virus. It remains too early to know whether infection with SARS‐CoV‐2 causes persistent olfactory dysfunction. However, given the scale of this pandemic, if SARS‐CoV‐2 does cause chronic olfactory loss in even a small portion of those infected, then the overall population prevalence could be quite large. This review provides a brief, practical overview of viral‐associated olfactory loss, realizing that evidence related to COVID‐19 will likely not be clear for some time. Our goal is to highlight the existence and importance of this condition and provide information geared for both providers and patients. Practical suggestions regarding evaluation and treatment will be provided, realizing that there may be constraints on medical resources and the nature of this pandemic remains dynamic.